“Fascism is once more at our doors, and we still refuse to see and treat it by its name: an interview with Cultural Philosopher Rob Riemen (Revista Cantareira, 2020)
Rob Riemen is the Director of Nexus Institute, an “independent international human rights research and policy center” and an interdisciplinary Dutch researcher. Even though he prefers to be regarded as a Cultural Philosopher, his studies and works expand into various areas of the humanities. In 2010, therefore at the beginning of global democratic recession wave, Riemen published a book called The Eternal Return of Fascism, in which he analyzes that fascism will always reappear as long as mass society exists, and that it needs to be addressed for what it is: fascism, without using intellectual juggling to give other names to undemocratic movements. In this interview he spoke on how fascism will always reapear through new faces, but maintaining some old characteristics that make it possible to still be comprehended as such. He also described fascism as the political version of nihilism, showing how it is based only in an obsession with power.